Performance analysis of multi-radio routing protocol in cognitive radio ad hoc networks under different path failure rate - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Hassan, Wan Haslina (IOP Publishing, 2013)
In recent years, Cognitive Radio (CR) technology has largely attracted significant studies and research. Cognitive Radio Ad Hoc Network (CRAHN) is an emerging self-organized, multi-hop, wireless network which allows unlicensed users to opportunistically access available licensed spectrum bands for data communication under an intelligent and cautious manner. However, in CRAHNs, a lot of failures can easily occur during data transmission caused by PU (Primary User) activity, topology change, node fault, or link degradation. In this paper, an attempt has been made to evaluate the performance of the Multi-Radio Link-Quality Source Routing (MR-LQSR) protocol in CRAHNs under different path failure rate. In the MR-LQSR protocol, the Weighted Cumulative Expected Transmission Time (WCETT) is used as the routing metric. The simulations are carried out using the NS-2 simulator. The protocol performance is evaluated with respect to performance metrics like average throughput, packet loss, average end-to-end delay and average jitter. From the simulation results, it is observed that the number of path failures depends on the PUs number and mobility rate of SUs (Secondary Users). Moreover, the protocol performance is greatly affected when the path failure rate is high, leading to major service outages.